Characterization of a monoclonal antibody that selectively recognizes a subset of Entamoeba histolytica isolates. - Bhattacharya, A (1990)
Monoclonal antibody 2D7.10 recognized an antigen present in seven of nine isolates of axenically cultured Entamoeba histolytica and absent in all other Entamoeba isolates studied. The antigen was absent in two isolates: 200:NIH and Rahman. All nine isolates belonged to pathogenic zymodeme II. Western blot (immunoblot) analysis and treatment with periodate and the proteolytic enzyme trypsin suggest that the antigen recognized by 2D7.10 is a carbohydrate moiety.